Learning Management and Learning Media Based on Local Wisdom at RA Ma'arif Inclusion Metro - Muhammad Yusuf (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2022)
Education has educational goals according to their respective levels and categories. The aim of education at the early childhood education level, in this case RA Inclusion Ma'arif 1 Metro City, which is included in the category of formal education, has a goal as a process of stimulating child development. In achieving this goal, good management is needed which includes planning, implementation and evaluation, especially in the learning aspects and the media used. This research is a field research with a descriptive qualitative approach, while in terms of data collection used observation, interviews and documentation with data analysis organizing, analyzing, and interpreting data. As for the results of the research and discussion of this study, namely in the management of learning, planning is carried out in the form of preparing curriculum sets including; PROTA, PROMES, RPPM, RPPH and learning academic calendar. While in the implementation aspect, using the RPPH guidelines to run. As for the process of evaluating the results of the implementation of learning is done through daily assessments, work and anecdotal notes. Furthermore, the management of learning media based on local wisdom is planned and implemented based on the RPPH and uses materials that are available and easily available around the home and school environment. Learning and media are managed for the benefit of all students, both ABK and non-ABK as a commitment to realizing inclusive education.